A Computer-based Training Intervention for Work Supervisors to Respond to Intimate Partner Violence - Nancy Glass; Tina Bloom; Nancy Perrin; W. Kent Anger (Safety and Health at Work, 2010)
Objectives: Intimate partner violence (IPV), commonly known as domestic violence is a problem throughout the world. An estimated 36% to 75% of employed abused woman are monitored, harassed and physically assaulted by their partners or ex-partners while trying to get to work and while at work. The objective of this research is to evaluate the effectiveness of interactive training to increase knowledge, change perceptions and develop an intention to address domestic violence that spills over into the workplace. Methods: Community-based participatory research approaches were employed to develop and evaluate an interactive computer-based training (CBT) intervention, aimed to teach supervisors how to create supportive and safe workplaces for victims of IPV. Results: The CBT intervention was administered to 53 supervisors. All participants reacted positively to the training, and there was a significant improvement in knowledge between pre- and post-training test performance (72% versus 96% correct), effect size (d) = 3.56. Feedback from focus groups was more productive than written feedback solicited from the same participants at the end of the training. Conclusion: Effective training on the impacts of IPV can improve knowledge, achieving a large effect size, and produce changes in perspective about domestic violence and motivation to address domestic violence in the workplace, based on questionnaire responses.